2006
DOI: 10.1111/j.1526-4637.2006.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Significant Placebo Analgesic Response in a Pilot Trial of Botulinum B in Patients with Hand Pain and Carpal Tunnel Syndrome

Abstract: Botulinum toxin B is not dramatically superior to placebo for the relief of CTS symptoms. Possible explanations of the improvements in each study group are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 29 publications
0
53
0
Order By: Relevance
“…The authors found no benefit from injection of rimabotulinumtoxinB on pain, sleep, or quality of life compared with the placebo [35].…”
Section: Review Brown Schütz and Simpsonmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors found no benefit from injection of rimabotulinumtoxinB on pain, sleep, or quality of life compared with the placebo [35].…”
Section: Review Brown Schütz and Simpsonmentioning
confidence: 96%
“…Bohluli et al published preliminary data of an uncontrolled, nonrandomized, open-label trial of 15 patients with a 6-month to 24-year history of refractory trigeminal neuralgia in which an unspecified preparation of BoNT-A was injected into trigger zones (50-100 U of BoNT-A at each trigger zone with an unspecified depth of injection) identified by patients and confirmed by [35] Tsai et al clinical examination and by response to lidocaine injection. Patients were evaluated at 1 week, 1 month and 6 months following injections.…”
Section: Trigeminal Neuralgiamentioning
confidence: 97%
“…These results do not allow us to discriminate the placebo effect that has proved to be significant in similar situations. 9 Our group successfully treated a patient with refractory chronic postthoracotomy pain with subcutaneous BTX-A. 30 We found only 1 case in the literature of chronic postthoracotomy pain with subcutaneous BTX-A.…”
Section: Miscellaneousmentioning
confidence: 96%
“…We found only 1 report of BTX type B used for neuropathic pain. 9 For this reason, our literature search focused on BTX-A.…”
mentioning
confidence: 99%
“…Tsai found that in five patients injected intracarpally with toxin, pain was better in three, but there was no change in electrophysiological investigations indicating only a placebo or nociceptor response. Breuer et al 65 found no difference in a randomized controlled trial between placebo and botulinum toxin in 20 carpal tunnel patients.…”
Section: Carpal Tunnel Syndromementioning
confidence: 98%